Mapping knowledge of the stem cell in traumatic brain injury: a bibliometric and visualized analysis - Deng, Tingzhen; Ding, Ruiwen; Wang, Yatao; Chen, Yueyang; Sun, Hongtao; Zheng, Maohua (Frontiers in Neurology, 2024)
Background Traumatic brain injury (TBI) is a brain function injury caused by external mechanical injury. Primary and secondary injuries cause neurological deficits that mature brain tissue cannot repair itself. Stem cells can self-renewal and differentiate, the research of stem cells in the pathogenesis and treatment of TBI has made significant progress in recent years. However, numerous articles must be summarized to analyze hot spots and predict trends. This study aims to provide a panorama of knowledge and research hotspots through bibliometrics. Method We searched in the Web of Science Core Collection (WoSCC) database to identify articles pertaining to TBI and stem cells published between 2000 and 2022. Visualization knowledge maps, including co-authorship, co-citation, and co-occurrence analysis were generated by VOSviewer, CiteSpace, and the R package “bibliometrix.” Results We retrieved a total of 459 articles from 45 countries. The United States and China contributed the majority of publications. The number of publications related to TBI and stem cells is increasing yearly. Tianjin Medical University was the most prolific institution, and Professor Charles S. Cox, Jr. from the University of Texas Health Science Center at Houston was the most influential author. The Journal of Neurotrauma has published the most research articles on TBI and stem cells. Based on the burst references, “immunomodulation,” “TBI,” and “cellular therapy” have been regarded as research hotspots in the field. The keywords co-occurrence analysis revealed that “exosomes,” “neuroinflammation,” and “microglia” were essential research directions in the future. Conclusion Research on TBI and stem cells has shown a rapid growth trend in recent years. Existing studies mainly focus on the activation mechanism of endogenous neural stem cells and how to make exogenous stem cell therapy more effective. The combination with bioengineering technology is the trend in this field. Topics related to exosomes and immune regulation may be the future focus of TBI and stem cell research.